DECISION-MAKING IN AN ORGANIZATION - pratiwi, Tia; Hayati, Fitri (Journal of Educational Administration, 2023)
The organization is a place for administrative activities. Here management becomes one of the organizational subsystems. Management becomes a technique or tool that drives the organization to achieve the desired goals. Related to the role of the manager, decision-making is one of the roles of the manager which is called the decision-making role. In organizations, decision-making is usually normal in organizations. The decision basically means the final result in the consideration of something that is practiced. Choice can also be interpreted as the best outcome when one of two or more alternatives is selected. Decision-making is a systematic approach to a problem by collecting facts and data or information related to the problem to determine the alternative that is calculated to be the right action. It is therefore understandable that the decision-making process requires high-quality information capable of determining alternative steps.